2011
DOI: 10.1016/j.jtcvs.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Expanding cardiac pseudotumor

Abstract: Cardiac calcified amorphous tumor (CAT) is a rare pseudoneoplastic mass composed of calcium deposits in a background of amorphous degenerating fibrin. Although the pathogenesis of this entity is not well understood CAT is a clinically important pseudoneoplasm because it often raises high suspicion for malignancy. CLINICAL SUMMARYA 75-year-old woman presented with episodic presyncope associated with palpitations. She was diabetic and hypertensive with a history of rheumatic fever with associated valvular dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…18 IPTs are predominantly composed of degenerating fibrin with central nodular calcium deposits, mild to moderate chronic inflammation, and degenerating blood elements and can even present as large mass. 19 RCC represents 3% to 4% of all cancers, with about 5% to 10% presenting as extension IVC with tumor thrombus. 20,21 Combined excision of renal mass and its extension into IVC and RA as done by us has also been described by others.…”
Section: International Journal Of Contemporary Medical Researchmentioning
confidence: 99%
“…18 IPTs are predominantly composed of degenerating fibrin with central nodular calcium deposits, mild to moderate chronic inflammation, and degenerating blood elements and can even present as large mass. 19 RCC represents 3% to 4% of all cancers, with about 5% to 10% presenting as extension IVC with tumor thrombus. 20,21 Combined excision of renal mass and its extension into IVC and RA as done by us has also been described by others.…”
Section: International Journal Of Contemporary Medical Researchmentioning
confidence: 99%
“…Further histologic examination revealed that CAT is a basically a conglomerate of several elements, including focal inflammation, chalky and nodular central calcium deposits, degenerating blood constituents and fibrin . While visible on echocardiography, it is nearly impossible to make a definitive diagnosis with imaging given the lack of any pathognomonic features . Figure reveals a typical echocardiographic appearance of CAT.…”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
“…In some cases, it can be mistaken for a valvular vegetation, especially if associated with preexisting MAC . In certain cases, obstruction of valves and embolization may occur . Surgery is diagnostic and curative in nearly all cases …”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
See 2 more Smart Citations